PENGEMBANGAN FILM ANIMASI BERBASIS RUMAH ADAT KAJANG LAKO UNTUK MENINGKATKAN KEMAMPUAN LITERASI MATEMATIS SISWA SMP - Fitriani Lianti; Husni Sabi; Novferma; Supian (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the importance of enhancing junior high school students' mathematical literacy through innovative and contextual learning media. The purpose of this study is to develop an educational animated film based on the ethnomathematics of the Kajang Lako traditional house to improve students mathematical literacy, specifically on the topic of Flat-Sided Three-Dimensional Geometry. The research method employed is a mixed methods approach utilizing Research and Development (R&D). This study focuses on evaluating the validity, practicality, and effectiveness of the developed product.The results indicate that .integrating the ethnomathematics of the Kajang Lako traditional house into the animated film successfully meets instructional standards. Based on expert evaluation, the material validity reached 81.3% and media validity reached 86.4%, both falling into the highly valid category. Furthermore, the product was deemed highly practical by both teachers and students during the learning process. The effectiveness test demonstrated that the animated film significantly improved students' mathematical literacy, as evidenced by an N-Gain score of 67%. Consequently, this animated film media is scientifically proven and highly suitable as an innovative alternative for mathematics learning for junior high school students.